Rancang Bangun Sistem Pengontrolan Ruang Pemulihan Pasca Operasi Berbasis Wireless Sensor Network - Yuni Imanniarti (Politeknik Negeri Malang, 2019)
The recovery room is a room in hospital, where patients are treated after they have undergone surgical operations and recovered from the effects of anesthesia. In recovery room, patients really need a comfort so that they don't experience physical and psychological stress too much. Comfort for everyone is different, but there are several factors that can make the room more comfortable. Therefore, it will take parameters for this research, namely temperature, humidity and lighting.In this study, we will discuss how to design a wireless sensor network system for controlling the recovery room after cesarean operation and how to test sensors on this system and how to display processing result data to a smartphone.This research will explain about the system description of room temperature and humidity, UV light and room light intensity based on wireless sensor network using 2 types of nodes, namely sink nodes and control sensor nodes and using the HC-12 wireless module as data sender and receiver between nodes. The data taken is related to the measurement result information data that will be accessed and displayed via Android application in realtime.From the system designed, the error value is obtained with an average temperature value on R1 of 1.16%, R2 is 2.64% and R3 is 5.36%, while for the humidity value on R1 is 3.70%, R2 is 9, 32% and R3 10.54%. For testing the communication distance of 10m, the delay value without barrier is 60 seconds, while with barrier, the delay value is 97 seconds.